Secondary battery and device including the same

By using thermally decomposed heat-absorbing materials in lithium batteries, the thermal decomposition reaction is used to absorb heat, which solves the problem of thermal runaway from lithium batteries and improves the safety performance and energy density of the battery.

CN119864560APending Publication Date: 2025-04-22NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311373175.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

High-energy density lithium batteries are prone to thermal runaway, resulting in safety problems. The prior art is difficult to effectively suppress thermal runaway without affecting other battery performance.

Method used

A thermally decomposed heat-absorbing material is used, which produces low-boiling compounds at the decomposition temperature, absorbs heat through the thermal decomposition reaction, eliminates local overheating, and inhibits thermal runaway.

Benefits of technology

Absorb more heat through chemical reactions, effectively eliminating local overheating of the battery and improving battery safety performance without significantly reducing energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864560A_ABST
    Figure CN119864560A_ABST
Patent Text Reader

Abstract

The present invention provides a secondary battery comprising an endothermic material comprising at least one of the structures of Formula I, Formula II, and Formula III # imgabs0 # wherein n is from 2 to 100,000 and R1, R2, R3, R4, R5, R6, R1 ', R2', R3 ', R4', R5 ', R6', R1 ", R2", R3 ", R4", R5 ", R6" are independently selected from the group consisting of H, F, C1-C6 alkyl, and fluorine-substituted C1-C6 alkyl, as well as a device comprising the secondary battery of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and in particular to a secondary battery and a device comprising the same. Background Art

[0002] With the development of lithium batteries, high energy density batteries have gradually become mainstream. Since high energy density batteries are prone to internal temperature rise and a series of reactions that eventually lead to thermal runaway of the battery, safety issues have gradually become a factor limiting the application of high energy density batteries. This makes how to suppress thermal runaway and thus improve battery safety an important direction for the current development of lithium batteries.

[0003] Currently, researchers have proposed many methods to inhibit thermal runaway, including adding flame retardants to the electrolyte and improving the thermal stability of the positive electrode through positive electrode coating and doping. However, these methods cannot significantly inhibit the occurrence of thermal runaway without significantly affecting other battery performance.

[0004] Therefore, there is a need in the art for a secondary battery that can effectively suppress local overheating through chemical reactions. Summary of the invention

[0005] In order to solve the above problems, an object of the present invention is to provide a secondary battery, the secondary battery comprising an endothermic material, the endothermic material comprising at least one of the structures of formula I, formula II and formula III,

[0006]

[0007] wherein, n is 2 to 100000, and R1, R2, R3, R4, R5, R6, R1', R2', R3', R4', R5', R6', R1", R2", R3", R4", R5", R6" are independently selected from H, F, C1-C6 alkyl and fluorine-substituted C1-C6 alkyl.

[0008] According to one embodiment of the present invention, the heat-absorbing material is a thermally decomposable compound, the heat-absorbing material can generate a low-boiling-point compound at a decomposition temperature, and the boiling point of the low-boiling-point compound is below 80°C.

[0009] The endothermic material according to the present invention can undergo a thermal decomposition reaction at high temperature, so that the branched part bound to the polymer main chain of the endothermic material is separated, and the reaction enthalpy of the thermal decomposition reaction and the phase change enthalpy of the low-boiling compound formed by the branched part are used to absorb heat, thereby eliminating local overheating to inhibit thermal runaway. Compared with the prior art that deals with violent side reactions and the heat generated in the late stage of the thermal runaway process, it is a more efficient way to cut off the accumulation of heat in the early stage of the thermal runaway process, that is, to eliminate local overheating. Since the heat that can be absorbed by chemical reactions is 1-2 orders of magnitude more than that of physical changes (phase changes), compared with the common endothermic absorption using phase change materials, the thermal decomposition reaction of the endothermic material of the present invention can absorb more heat, so that the local overheating of the battery can be effectively eliminated with a small amount of addition.

[0010] The endothermic material according to the present invention, by means of the simple structure of Formula I, Formula II and Formula III, significantly improves the safety performance of the battery without significantly reducing the energy density of the battery and does not have a negative impact on the performance of the secondary battery. In particular, in view of the high heat absorption capacity of the endothermic material, only a very small amount of endothermic material relative to the active material needs to be added to the secondary battery of the present invention. Therefore, in some embodiments, although the low-boiling point compounds generated by the thermal decomposition reaction of the endothermic material of the present invention at high temperature can volatilize and generate gases, these gases do not visibly affect the thickness expansion rate or safety performance of the battery.

[0011] According to one embodiment of the present invention, the thermal decomposition reaction of the endothermic material occurs at 50°C to 130°C.

[0012] According to one embodiment of the present invention, the thermal decomposition reaction is a reversible thermal decomposition reaction. According to one embodiment of the present invention, the endothermic material produces a low boiling point compound and a polymer at a decomposition temperature, and when the temperature is lower than the decomposition temperature, the low boiling point compound and the polymer can react to form the endothermic material. The endothermic material of the present invention reacts at high temperatures to absorb heat, and at low temperatures to release heat by a corresponding reversible reaction, thereby ensuring that the endothermic material reacts repeatedly at the same position of the battery, and the gas generated by the decomposition reaction will not exert pressure on the battery packaging for a long time.

[0013] According to one embodiment of the present invention, the heat absorbing material comprises at least one of the following structures:

[0014]

[0015]

[0016] According to one embodiment of the present invention, the low boiling point compound comprises at least one of furan, 2-methylfuran and 2-ethylfuran. In addition to absorbing heat through the chemical reaction of the endothermic material, the present invention further absorbs heat by volatilization of the low boiling point compound generated after the chemical reaction of the endothermic material.

[0017] According to one embodiment of the present invention, the reaction rate of thermal decomposition can be regulated by R1-R6, R1'-R6', R1"-R6". For example, the smaller the steric hindrance of R1-R6, the faster the reaction rate. Compared with the compound of formula I-4 in which R6 is isobutyl, the compound of formula I-3 in which R6 is methyl has a higher reaction rate and heat absorption efficiency, thereby being able to eliminate local hot spots of the battery in a shorter time.

[0018] According to one embodiment of the present invention, the endothermic heat Q of the endothermic material satisfies: Q is greater than 200 J / g. According to one embodiment of the present invention, the endothermic heat Q of the endothermic material satisfies: Q is greater than 300 J / g. According to a preferred embodiment of the present invention, the endothermic heat Q of the endothermic material satisfies: Q is greater than 400 J / g.

[0019] According to one embodiment of the present invention, the reversible thermal decomposition reaction is, for example, a Diels-Alder reaction, taking into account the heat absorption capacity, the temperature at which the thermal decomposition reaction is triggered, and the compatibility of the heat absorption material with the electrolyte and the positive and negative electrodes. After the reaction, small molecules with low boiling points are generated, such as furan, 2-methylfuran, 2-ethylfuran, etc. These small molecules with low boiling points volatilize under heating and take away heat at the same time.

[0020] The reversible reactions that may be involved in the endothermic material according to the present invention include but are not limited to hydrogen bonds breaking at high temperatures and / or reorganizing at low temperatures; sulfur-sulfur bonds breaking at high temperatures and / or re-bonding at low temperatures; cyclohexene undergoing a Diels-Alder reverse reaction at high temperatures to generate dienes and monoenes and / or undergoing a Diels-Alder reaction at low temperatures to regenerate cyclohexene. According to one embodiment of the present invention, the compound of formula I-1 may undergo the following reaction at the decomposition temperature,

[0021] According to one embodiment of the present invention, the compound of formula I-2 may undergo the following reaction at the decomposition temperature,

[0022]

[0023] According to one embodiment of the present invention, the compound of formula I-3 may undergo the following reaction at the decomposition temperature,

[0024]

[0025] According to one embodiment of the present invention, the compound of formula I-4 may undergo the following reaction at the decomposition temperature,

[0026]

[0027] According to one embodiment of the present invention, the compound of formula II-1 may undergo the following reaction at the decomposition temperature,

[0028]

[0029] According to one embodiment of the present invention, the compound of formula III-1 may undergo the following reaction at the decomposition temperature,

[0030]

[0031] According to some embodiments of the invention, the endothermic material is insoluble in the electrolyte.

[0032] According to some embodiments of the present invention, the endothermic material according to the present invention is disposed in a designated portion of a secondary battery depending on a triggering mechanism of thermal runaway.

[0033] According to some embodiments of the present invention, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the endothermic material is disposed in at least one of the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte.

[0034] According to some embodiments of the present invention, the positive electrode sheet includes a positive electrode active material and the endothermic material, wherein a mass ratio of the endothermic material to the positive electrode active material is 0.1:100 to 3:100.

[0035] According to some embodiments of the present invention, the negative electrode sheet includes a negative electrode active material and the heat absorbing material, wherein a mass ratio of the heat absorbing material to the negative electrode active material is 0.1:100 to 3:100.

[0036] According to some embodiments of the present invention, the positive electrode sheet includes a positive active material layer, and the heat absorption material is disposed on a surface of the positive active material layer, for example, on a surface of the positive active material layer facing the positive current collector or away from the positive current collector.

[0037] According to some preferred embodiments of the present invention, considering that the thermal runaway process of most high energy density batteries is triggered by the negative electrode side, the heat absorbing material according to the present invention is disposed at the negative electrode.

[0038] According to some embodiments of the present invention, the negative electrode sheet includes a negative active material layer, and the heat absorption material is disposed on the surface of the negative active material layer, for example, on the surface of the negative active material layer facing the negative current collector or away from the negative current collector.

[0039] According to some embodiments of the present invention, the heat absorbing material is disposed on a side of the separator close to the negative electrode plate, wherein the mass ratio of the heat absorbing material to the negative electrode active material is 0.1:100 to 3:100;

[0040] According to some embodiments of the present invention, the heat absorbing material is disposed on a side of the separator close to the positive electrode plate, wherein the mass ratio of the heat absorbing material to the positive electrode active material is 0.1:100 to 3:100.

[0041] According to some embodiments of the present invention, the electrolyte comprises an endothermic material, wherein the content of the endothermic material is 1 wt % to 20 wt % based on the total weight of the electrolyte.

[0042] Another object of the present invention is to provide a device, which comprises the secondary battery according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.

[0044] Figure 1 Schematically shows the process of thermal decomposition of the endothermic material according to the present invention;

[0045] Figure 2 A differential scanning calorimetry diagram of an endothermic material according to the present invention is schematically shown.

[0046] Reference numerals list

[0047] 100 Heat absorbing material

[0048] 101 Polymer backbone

[0049] 102 Polymer branching before thermal decomposition

[0050] 110 Endothermic material after thermal decomposition

[0051] 112 Polymer branched chain after thermal decomposition

[0052] 120 Low boiling point compounds DETAILED DESCRIPTION

[0053] The foregoing and other objects, components and advantages will become apparent from the following more detailed description of specific embodiments as illustrated and exemplified in the accompanying drawings, wherein like reference numerals, designations, etc. represent like parts, components or features of the specific embodiments.

[0054] In terms of its scope of use, the terms "including", "comprising" and "having" or any variation thereof as used in the claims and description herein will be considered to indicate an open group that can include unspecified other elements. The terms "one", "a kind of" and the words in the singular form should be understood to include the plural form of the same word, so that these terms represent that one or more things are provided. The terms "at least one" and "one or more" can be used interchangeably. The term "single" is used to indicate one and only one of something. Similarly, when a specific number of things is needed, other specific integer values, such as "two" will be used. The terms "preferably", "preferred", "preferably", "optionally", "can" and similar terms are used to indicate that the quoted items, conditions or steps are optional (that is, not required) features in the embodiment. Unless otherwise stated, the range described as "between a and b" includes the values ​​of "a" and "b".

[0055] Although various improvements have been described herein with reference to specific embodiments of the invention, it should be understood that such description is by way of illustration only and should not be construed as limiting the scope of any claimed invention. Accordingly, the scope and content of any claimed invention will be limited solely by the terms of the appended claims in their current form or as amended during prosecution or in any continuation of application. In addition, it should be understood that, unless otherwise indicated, the features of any specific embodiment discussed herein may be combined with one or more features of any one or more embodiments otherwise discussed or considered herein.

[0056] 1. Heat absorbing materials

[0057] In a first aspect, the present invention provides an endothermic material, which is a thermally decomposable compound. The endothermic material can generate a low-boiling-point compound at a decomposition temperature, and the boiling point of the low-boiling-point compound is below 80°C.

[0058] In some embodiments, the endothermic material comprises at least one of the structures of Formula I, Formula II, and Formula III,

[0059]

[0060] wherein n is 2 to 100000, and R1, R2, R3, R4, R5, R6, R1', R2', R3', R4', R5, R6', R1", R2", R3", R4", R5", R6" are independently selected from H, F, C1-C6 alkyl and fluorine-substituted C1-C6 alkyl.

[0061] Figure 1 A schematic diagram of thermal decomposition of an endothermic material is shown, wherein the endothermic material 100 includes a polymer main chain 101 and a branch chain 102, and generates a low-boiling point compound 120 after being heated.

[0062] In some embodiments, the polymer main chain in the structure of Formula I, Formula II and Formula III enables the endothermic material to decompose in time at the decomposition temperature and absorb heat from the surrounding environment. On the other hand, the presence of the polymer main chain prevents the endothermic material from dissolving in the electrolyte, so that the endothermic material increases the battery safety while not negatively affecting the ion conductivity inside the battery.

[0063] In some embodiments, n is 2, 4, 6, 8, 10, 50, 100, 500, 1000, 5000, 10000, 50000, 100000, or any interval thereof.

[0064] In some embodiments, the endothermic material has a number average molecular weight of 5,000 to 50,000, for example, 5,000, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, or any interval thereof.

[0065] In some embodiments, the endothermic material has a number average molecular weight of 10,000 to 15,000.

[0066] In some embodiments, the endothermic heat capacity Q of the endothermic material satisfies: Q is greater than 200 J / g, for example, 210 J / g, 220 J / g, 240 J / g, 260 J / g, 280 J / g, 300 J / g, 320 J / g, 340 J / g, 360 J / g, 380 J / g, 400 J / g, 420 J / g, 440 J / g, 460 J / g, 480 J / g, 490 J / g, 500 J / g, 510 J / g, 520 J / g, 530 J / g or any interval thereof.

[0067] In some embodiments, the endothermic heat amount Q of the endothermic material satisfies: Q is greater than 300 J / g. In some embodiments, the endothermic heat amount Q of the endothermic material satisfies: Q is greater than 400 J / g.

[0068] In some embodiments, the decomposition temperature is 50°C to 130°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, or any interval thereof.

[0069] 2. Secondary battery

[0070] In a second aspect, the present invention provides a secondary battery comprising the endothermic material described in the first aspect. The secondary battery is a lithium secondary battery or a sodium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, a lithium ion polymer secondary battery, a sodium ion secondary battery, a sodium polymer secondary battery or a sodium ion polymer secondary battery.

[0071] In some embodiments, the secondary battery of the present invention includes a positive electrode, a negative electrode and a separator. The negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, and the positive electrode includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material.

[0072] In some embodiments, the endothermic material described in the first aspect is arranged on the negative electrode, in some embodiments, the endothermic material described in the first aspect is arranged on the positive electrode, in some embodiments, the endothermic material described in the first aspect is arranged on the separator, and in some embodiments, the endothermic material described in the first aspect is arranged in the electrolyte.

[0073] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.

[0074] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide, and lithium titanate.

[0075] In some embodiments, the positive electrode active material layer further includes a binder, which includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.

[0076] In some embodiments, the positive electrode active material layer further includes a conductive agent, and the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based materials are selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based materials are selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0077] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector, such as copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0078] In some embodiments, the negative electrode active material may include a material that can reversibly intercalate / deintercalate lithium ions, lithium metal, a lithium metal alloy, a material that can dope / de-dope lithium, or a transition metal oxide, such as Si, SiOx (0 < x < 2), and other materials. The material that can reversibly intercalate / deintercalate lithium ions may be a carbon material. The carbon material may be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable secondary batteries. Examples of the carbon material include crystalline carbon, amorphous carbon, and combinations thereof. The crystalline carbon may be amorphous or in the form of plates, flakes, spheres, or fibers of natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, etc. Both low-crystalline carbon and high-crystalline carbon can be used as the carbon material. As the low-crystalline carbon material, soft carbon and hard carbon are generally included. As the high-crystalline carbon material, natural graphite, crystalline graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbead, mesophase pitch, and high-temperature calcined carbon (such as petroleum or coke derived from coal tar pitch) are generally included.

[0079] In some embodiments, the negative electrode active material layer further includes a binder, and the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc.

[0080] In some embodiments, the negative electrode active material layer further includes a conductive agent, and the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based materials are selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based materials are selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0081] The secondary battery of the present invention further comprises a separator. The material and shape of the separator used in the embodiment of the present invention are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator comprises a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present invention.

[0082] According to some embodiments of the present invention, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene and polyethylene terephthalate. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0083] According to some embodiments of the present invention, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0084] According to some embodiments of the present invention, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0085] According to some embodiments of the present invention, the polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0086] The secondary battery of the present invention further comprises an electrolyte. The electrolyte that can be used in the present invention can be an electrolyte known in the prior art.

[0087] According to some embodiments of the present invention, the electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent in the electrolyte of the present invention may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present invention is not limited, and it may be any electrolyte known in the prior art. The additive of the electrolyte according to the present invention may be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate or ethyl propionate. In some embodiments, the organic solvent includes an ether solvent, for example, including at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2)(LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.

[0088] In some embodiments, the secondary battery is a lithium-ion battery.

[0089] 3. Device

[0090] In a third aspect, the present invention further provides a device, which comprises the secondary battery according to the second aspect of the present invention.

[0091] The device of the present invention is not particularly limited. In some embodiments, the device of the present invention includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0092] 4. Test Method

[0093] Heat absorption capacity test of heat absorbing materials

[0094] The reaction enthalpy, phase transition temperature of the product and the thermal effect of the endothermic material were measured by differential scanning calorimeter NETZSCH DSC3500. About 10 mg of the sample was sealed in a high-pressure crucible. The temperature was raised from -40°C to 180°C at a rate of 10°C / min to obtain the thermal effect of the material.

[0095] Battery temperature test

[0096] A PI heating film of set size is placed inside the battery to simulate the local hot spots that may occur in the battery. The PI heating film is powered by a programmable DC power supply, and the heating power of the PI heating film is set to 5W. After heating for 1000s, ultra-fine thermocouples are placed at the center and surface of the battery to detect the temperature of each part.

[0097] Cycle retention capability

[0098] The battery was charged to 4.25V at 1C constant current and constant voltage, with a cut-off current of 1 / 20C, and then discharged to 2.5V at 1C constant current. The cycle was repeated until the discharge capacity of the battery was less than or equal to 80% of the initial capacity. The number of cycles at this time was recorded to indicate the cycle retention capacity (number of cycles).

[0099] Example 1

[0100] Preparation of the negative electrode: The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, the thickener sodium carboxymethyl cellulose, and the polyacrylic acid are mixed in a weight ratio of 95:2:1.5:1:1:0.5, deionized water is added, and the negative electrode slurry is obtained after stirring. The negative electrode slurry is evenly coated on an 8 μm thick negative electrode current collector copper foil to form a negative electrode active material layer, and then dried and rolled to obtain the negative electrode.

[0101] Preparation of positive electrode: LiNi 0.9 Co 0.05 Mn 0.05 O2, conductive agent carbon nanotube / acetylene black, binder polyvinylidene fluoride PVDF, by weight ratio LiNi 0.9 Co 0.05 Mn 0.05 O2: CNT / Super-P: PVDF=95:

[0102] 2.0 / 1.0:2 was fully mixed in an N-methylpyrrolidone solvent system and then coated on a 12 μm thick positive electrode current collector aluminum foil to form a positive electrode active material layer; and the positive electrode was obtained after drying and rolling.

[0103] Preparation of electrolyte: In an argon-protected glove box (water content <1ppm, oxygen content <1ppm), ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 20:5:45, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and the electrolyte was obtained after stirring evenly.

[0104] Preparation of separator: A 9 μm thick polyethylene (PE) separator was used.

[0105] Coating of endothermic material: The endothermic material of formula I-1 and N-methylpyrrolidone are mixed at a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the endothermic material of formula I-1 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 1%.

[0106] Assembly of lithium-ion batteries: stack the positive electrode, separator, and negative electrode in sequence, with the separator between the positive and negative electrode sheets, and then place them in the outer packaging foil aluminum-plastic film after winding and welding the pole ears, and inject the above-mentioned electrolyte. After vacuum packaging, standing, formation, shaping, and capacity testing, a lithium-ion battery is obtained.

[0107] Example 2

[0108] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0109] The endothermic material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the side of the separator close to the negative electrode, and after drying, a separator containing the endothermic material of formula I-1 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 1%.

[0110] Example 3

[0111] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0112] The endothermic material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the endothermic material of formula I-2 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 1%.

[0113] Example 4

[0114] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0115] The endothermic material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the endothermic material of formula I-3 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 1%.

[0116] Example 5

[0117] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0118] The endothermic material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the endothermic material of formula I-4 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 1%.

[0119] Example 6

[0120] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0121] The heat absorbing material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the heat absorbing material of formula II-1 is obtained, and the mass ratio of the heat absorbing material to the negative electrode active material is 1%.

[0122] Example 7

[0123] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0124] The heat absorbing material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the heat absorbing material of formula III-1 is obtained, and the mass ratio of the heat absorbing material to the negative electrode active material is 1%.

[0125] Example 8

[0126] The method is substantially the same as Example 1, except that the coating of the heat absorbing material is performed as follows:

[0127] The endothermic material of formula I-1 and N-methylpyrrolidone are mixed in a weight ratio of 1:9 to obtain a slurry. The slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode sheet containing the endothermic material of formula I-1 is obtained, and the mass ratio of the endothermic material to the negative electrode active material is 2%.

[0128] Comparative Example 1

[0129] The method is substantially the same as that of Example 1, except that the coating of the heat absorbing material is not performed.

[0130] The heat absorbing capacity of the heat absorbing material of formula I-1 was tested, and the results are shown in Figure 2 It can be seen that the endothermic material of formula I-1 has obvious endothermic capacity at a temperature of 50° C., and from the peak area, it can be seen that the endothermic material of formula I-1 has an endothermic capacity of 499.4 J / g.

[0131] The batteries obtained in Examples 1-8 and Comparative Example 1 were subjected to a battery temperature test and a battery cycle test. The test results are shown in Table 1.

[0132] Table 1

[0133]

[0134] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.

Claims

1. A secondary battery, characterized in that: The secondary battery includes an endothermic material, wherein the endothermic material includes at least one of a structure of Formula I, a structure of Formula II, and a structure of Formula III. wherein n is 2 to 100000, and R1, R2, R3, R4, R5, R6, R1', R2', R3', R4', R5', R6', R1", R2", R3", R4", R5", R6" are independently selected from H, F, C1-C6 alkyl and fluorine-substituted C1-C6 alkyl.

2. The secondary battery according to claim 1, characterized in that: The heat absorbing material comprises at least one of the following structures: Wherein, n is 2 to 100,000.

3. The secondary battery according to claim 1, characterized in that: The endothermic material generates low boiling point compounds at a decomposition temperature, and the boiling point of the low boiling point compounds is below 80°C.

4. The secondary battery according to claim 3, characterized in that: The decomposition temperature is 50°C to 130°C.

5. The secondary battery according to claim 3, characterized in that: The low boiling point compound includes at least one of furan, 2-methylfuran and 2-ethylfuran.

6. The secondary battery according to claim 1, characterized in that: The endothermic material generates a low boiling point compound and a polymer at a decomposition temperature, and when the temperature is lower than the decomposition temperature, the low boiling point compound and the polymer may react to generate the endothermic material.

7. The secondary battery according to claim 1, characterized in that: The heat absorption amount Q of the heat absorption material satisfies: Q is greater than 300 J / g.

8. The secondary battery according to claim 1, characterized in that: The heat absorption amount Q of the heat absorption material satisfies: Q is greater than 400 J / g.

9. The secondary battery according to claim 1, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, the negative electrode sheet comprises a negative electrode active material, and wherein at least one of the following conditions is satisfied: (i) the positive electrode sheet comprises a positive electrode active material and the endothermic material, wherein the mass ratio of the endothermic material to the positive electrode active material is 0.1:100 to 3:100; (ii) the negative electrode sheet comprises a negative electrode active material and the endothermic material, wherein the mass ratio of the endothermic material to the negative electrode active material is 0.1:100 to 3:100; (iii) the heat absorbing material is disposed on a side of the separator close to the negative electrode plate, wherein the mass ratio of the heat absorbing material to the negative electrode active material is 0.1:100 to 3:100; (iv) the endothermic material is disposed on a side of the separator close to the positive electrode plate, wherein the mass ratio of the endothermic material to the positive electrode active material is 0.1:100 to 3:100; (v) The electrolyte contains an endothermic material, wherein the content of the endothermic material is 1 wt % to 20 wt % based on the total weight of the electrolyte.

10. A device, characterized in that: The device comprises the secondary battery according to any one of claims 1 to 9.